Pathways to adolescent childbearing among Kaqchikel women in Guatemala. Issue 10 (3rd October 2017) - Lemon, Emily; Hennink, Monique; Can Saquic, Nely Amparo
Abstract: One-in-five children in Guatemala is born to a mother aged 15–19 years, which poses social, economic and health risks to both mother and child. In Guatemala, adolescent childbearing is directly associated with education, ethnicity and poverty, which increases vulnerability among Indigenous young women living in poverty. This study examines the context and experiences of adolescent childbearing from the perspectives of young mothers in the Kaqchikel Indigenous ethnic group of Sololá, Guatemala. Data were collected in 19 qualitative in-depth interviews with women who had given birth to one or more children when aged 15 to 19 years. Grounded theory and narrative analysis were used to develop a conceptual framework of the process and influences on childbearing. Four distinct pathways were identified, which were influenced by gender expectations, limited communication about sex and stigma around sex. The study identifies key sociocultural influences that lead to adolescent childbearing and reveals variability within these. Identifying distinct pathways to early childbearing and their influences enables a clearer understanding of potential opportunities to interrupt these pathways with culturally relevant policies and programmes, in particular those that promote gender equality and intergenerational communication about sex.